Characteristics of Escherichia coli Isolated from Intestinal Microbiota Children of 0–5 Years Old in the Commune of Abomey-Calavi. (6th June 2022) - Sina, Haziz; Dah-Nouvlessounon, Durand; Adjobimey, Tomabu; Boya, Bawa; Dohoue, Ghislaine M. C.; N'tcha, Christine; Chidikofan, Violette; Baba-Moussa, Farid; Abdoulaye, Idrissou; Adjanohoun, Adolphe; Baba-Moussa, Lamine
Abstract : Escherichia coli is a commensal bacterium and one of the first bacteria to colonize the digestive tract of newborns after birth. It is characterized by great versatility and metabolic flexibility that allows its survival in different niches. The present study aims at analyzing the diversity of E. coli strains isolated from the intestinal microbiota of children aged from 0 to 5 years in the commune of Abomey-Calavi in Benin. For this purpose, a descriptive and analytical cross-sectional study was conducted. A total of 135 stool samples were collected from the pediatric clinic of Abomey-Calavi. Microbiological analyses were performed according to standard microbiology analytical techniques. The molecular characterization of E. coli was performed by investigating eight genes (dinB, icdA, pabB, polB, putP, trpA, trpB, and uidA) using the PCR technique. The results showed that the average loading rate on stool samples was 3.74 × 10 7  CFU/g for TAMF. A total of 7 species of bacteria were identified at different proportions: Staphylococcus spp (55.36%), E. coli (14.29%), Klebsiella ornithinolytica (12.5%), Serratia odorifera (5.36%), and Enterobacter aerogenes (5.36%). Interestingly, isolated E. coli presented a resistance of 100% to cefotaxime and aztreonam. In addition, resistances of 95.24% and 50% were observed against erythromycin and nalidixic acid, respectively. The molecular characterization of the isolated E. coli strains allowed us to discover another molecular variation within the isolated strains. Genes encoding the enzymes isocitrate dehydrogenase (icd) and DNA polymerase II (polB) were detected at 96.30% in the isolated E. coli strains. Moreover, the genes encoding the enzymes beta-D-glucuronidase ( uid A) and DNA polymerase (dinB) were detected at 88.89% in the isolated E. coli strains. Interestingly, 81.48%, 85.19, 92.59%, and 100% of isolated E. coli strains expressed the genes encoding the enzymes tryptophan synthase subunit A (trpA), proline permease ( put P), p-aminobenzoate synthase, and tryptophan synthase subunit B (trpB), respectively. The diversity of E. coli strains reflects the importance of regulatory mechanisms in the adaptation of bacteria to the gut microbiota.